PENGARUH PEMBIAYAAN SYARIAH, PEMASARAN, DAN LITERASI KEUANGAN TERHADAP OMZET USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA SAAT PANDEMI COVID-19 - Afif Abdurrasyid Ahmad; Bahtiar Fitanto (Islamic Economics and finance in Focus, 2024)
This study examines the impact of Sharia Financing, Marketing, and Financial Literacy on the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Kota Malang. The findings indicate that these three variables have a positive simultaneous influence on MSME revenue. Sharia Financing were identified as the variable with the most significant effect, suggesting that improved access to capital can enhance MSME income. Furthermore, marketing expenses contribute to revenue growth by attracting attention and building consumer loyalty. Lastly, a high level of financial literacy plays a role in effective financial management and mature business planning. This research provides insights that sharia financing, marketing, and financial literacy are key factors that can support the growth and competitiveness of MSMEs in Malang City.